2D flow fields in fixed-bed reactor design: a robust methodology for continuum models. (23rd November 2019) - Donaubauer, Philipp J.; Schmalhorst, Leonhard; Hinrichsen, Olaf
Graphical abstract: Highlights: Coupling of 2D flow field and chemical reaction in fixed bed continuum model. Efficient solution of momentum balance by staggered finite difference grid. Pseudo-homogeneous reactor model accounting for 2D dispersive transport. Critical assessment of artificial boundary condition at inlet domain discontinuity. Pellet shape and radial porosity profile have strong impact on reactor performance. Abstract: In combination with computationally demanding, but steadily developing discrete particle simulation techniques, new areas of application for the fixed-bed continuum models, like in silico determination of transport parameters, become accessible. Within this study, we present a pseudo-homogeneous continuum model fully accounting for 2D fluid flow, heat and species dispersion in axial and radial direction and apply it to four configurations of packed beds. Application of different discretization techniques for fluid flow as well as heat and species transport provide an efficient and robust solution strategy. Beds of ideal spheres exhibited deviating conversion behavior due to strong oscillation in the radial flow profile. Moreover, the importance of adequate coupling of fluid flow and chemical reaction is highlighted by a variation of reaction stoichiometry. This theoretical evaluation of the continuum approach provides valuable insights on the interplay of fluid flow and chemical reaction in fixed-bed reactors.